2007
DOI: 10.1111/j.1469-1795.2007.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differentiation between the two remaining populations of the critically endangered Mediterranean monk seal

Abstract: The Mediterranean monk seal Monachus monachus, is a critically-endangered species of which only two populations, separated by c. 4000 km, remain: the eastern Mediterranean (150-300 individuals) and the Atlantic/western Sahara populations (100-130 individuals). We measured current levels of nuclear genetic variation at 24 microsatellite loci in 12 seals from the eastern Mediterranean and 98 seals from the western Sahara population and assessed differences between them. In both populations, genetic variation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 62 publications
(66 reference statements)
3
36
2
1
Order By: Relevance
“…Genetic analyses of mitochondrial and nuclear DNA (Pastor et al. , , Karamanlidis et al. ) have shown that, as a consequence of severe population bottlenecks and population fragmentation, all monk seal subpopulations exhibit low levels of genetic diversity.…”
Section: Geneticsmentioning
confidence: 99%
“…Genetic analyses of mitochondrial and nuclear DNA (Pastor et al. , , Karamanlidis et al. ) have shown that, as a consequence of severe population bottlenecks and population fragmentation, all monk seal subpopulations exhibit low levels of genetic diversity.…”
Section: Geneticsmentioning
confidence: 99%
“…Allen et al, 1995;Robertson & Gemmell, 2005;Pastor et al, 2007). To be cautious, this locus was removed from all further analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative genetic studies among populations, using mtDNA and nuclear microsatellite loci, showed two genetically differentiated populations: one from the eastern Mediterranean and one from the Atlantic/Western Sahara (Stanley and Harwood , Pastor et al . ). The geographic separation of the populations has led to the suggestion of a taxonomic separation of this species based on the differences in skull morphologies between the Mediterranean monk seals in the eastern Mediterranean, and those from the Atlantic and western Mediterranean (van Bree ).…”
mentioning
confidence: 97%
“…However, these studies showed that the genetic differences are most likely due to reproductive isolation of the two populations, and are not sufficient to permit a significant taxonomic differentiation of two distinct subspecies (Stanley and Harwood , Pastor et al . ).…”
mentioning
confidence: 97%
See 1 more Smart Citation